Penerapan Evidence-Based Nursing Dalam Pencegahan Luka Tekan Pada Pasien CVA Melalui Mobilisasi dan Skin Barrier Hidrokoloid - Eppy Setiyowati; Febi Ariska Putri; Zubaidi Zubaidi; Samsudi Samsudi (Universitas Pahlawan Tuanku Tambusai, 2026)
CVA patients experience bed rest which is quite long and continuous, which can cause the protrusion area to experience decreased blood circulation, circulation and absorption of nutrients and sufficient leukocytes. This will lead to tissue ischemia and subsequent infection, damage to the integrity of the skin tissue, namely, pressure injury or pressure sores. The purpose of this study was to analyze the description of nursing care in CVA patients with the application of mobilization support and care for skin integrity using a hydrocolloid skin barrier to overcome the risk of pressure ulcers in CVA patients in Room 7 RSPAL Dr Ramelan Surabaya. The research design of this final scientific work used the case method, with the subject being 1 patient with pressure ulcer risk nursing problems with a medical diagnosis of CVA. The research was conducted in Room 7, RSPAL Dr. Ramelan Surabaya, for 3 days, using data collection methods including comprehensive assessment, diagnosis determination, intervention determination, action implementation, and evaluation. The results of a case study on CVA with nursing problems at risk of pressure sores showed that after being given support for mobilization and skin integrity care (SIKI) therapy with bed transfer mobilization and administration of hydrocolloid skin barrier, pressure injury could be prevented, and the risk of pressure sores was reduced, and skin and tissue integrity increased. Nurses are expected to be able to implement and recommend the application of bed rest, mobilization, and administration of hydrocolloid skin barrier related to modification of care in addressing the risk of pressure sores.